PROBLEMS IN LEARNING READING (Case Study: Islamic Banking Students of IAIN Bukittinggi) - Widya Syafitri (Jurnal Educative: Journal of Educational Studies, 2018)
Teaching or learning Reading in ESP context is not an easy task. It was proved, especially for the fourth semester students of Islamic banking in IAIN Bukittinggi that many problems found. The research was a descriptive qualitative. It was aimed to analyze problem in reading. The data was gotten through interview to the lecturer and questionnaire distributed to the student. The result of the research showed that reading problems in ESP context based on indicator were: The first, a few students had problems related to indicator Negative Expectations like problems in recalling information after reading. The second, some the students had problems with processing information. The third, a half students had problem about topic and genre, limited vocabulary knowledge, lack of familiarity with the subject matter, difficulty level of the text (readability), weak verbal reasoning. The last, most of the students got difficulty at lack of fluency point, use of language level, inadequate use of effective reading strategies. Keywords: Reading problems, Islamic banking students, ESP